The Meaning of Repentance According to Imam Ghazali and Semantic Analysis in the Qur'an: A Comprehensive Study - Nabilah Nuraini (Westscience Press, 2024)
This study investigates the meaning of repentance as articulated by Imam Ghazali and its semantic representation in the Qur'an. By analyzing Imam Ghazali's interpretation of